Customer satisfaction on restructuring retail banking business model of BRAC Bank ltd. (supreme and excel banking) - Mushfiq, Takrim (BRAC University, 2013)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.